Effect of Polyphenol Extract from Malaysian Cocoa Powder on Plasma Lipid in Induced Rabbit Hypercholesterolemia Model - Addnan, Faizul Helmi (2007)
It is estimated that by 2010, cardiovascular disease (CVD) will be the leading cause of death in developing countries. In Malaysia, heart disease and disease of pulmonary circulation is the second major killer, making up 14.31% of total mortality reported in Ministry of Health (MOH), hospitals. Population studies have shown that plant polyphenol is inversely correlated with mortality from cardiovascular disease and numerous dietary flavonoids have been shown to beneficially impact toward atherosclerosis, including lipoprotein oxidation, blood platelet aggregation and vascular reactivity. There were many studied had reported that cocoa flavonoids had shown the similar degree towards being protective against CVD due to: antioxidant, anti-platelet, anti-inflammatory effects, as well as increasing HDL-c, lowering blood pressure and improving endothelial. However, the study on the effect of cocoa polyphenols on atherosclerotic plaque formation is to be documented. The present study was aimed to investigate the protective effects of polyphenol extract (CE) prepared from Malaysian cocoa powder against hypercholesterolemia atherosclerosis. Male New Zealand White rabbits were fed with the experimental diets for 12 weeks. Plasma total cholesterol (TC) increased up to week 12 for a group fed with diet enriched with 1% of cholesterol. Plasma TC were significantly decreased (p < 0.01) from 5 to 12 week when CE was administered at a dosage of 300, 600 and 800 mg/kg body weight/day. Significant increament (p < 0.01) and significant decreament (p < 0.01) in plasma high density lipoprotein cholesterol (HDL-c) was observed from 0 to 5 week and from 5 to 12 week, respectively for groups administered with CE. Plasma low density lipoprotein cholesterol (LDL-c) was significantly increased (p < 0.001) from initial to 5 week, and then decreased (p < 0.01) from 5 to 12 week in the group administered with CE, except for the 300 mg CE group. Compared to the standard laboratory diet, cholesterol–enriched diet increased aortic atherosclerosis formation, hepatic superoxide dismutase (SOD), hepatic glutathione peroxidase (GSHPx), hepatic malondialdehyde (MDA), and kidney GSHPx. Administered with 800 mg of CE to rabbits fed with cholesterol-enriched diet showed significant increased (p < 0.05) and significant decreased (p < 0.05) for activities of hepatic GSHPx and MDA concentration, respectively. Significant decreased (p < 0.05) in MDA concentration and significant increased (p < 0.05) for activities of hepatic catalase (CAT) was observed in groups of 600 mg CE and 300 mg CE, respectively. Approximately, 50 % area of atherosclerotic lesion in the rabbits fed with cholesterolenrich diet could be reduced by administering with CE. The effectiveness of CE against hypercholesterolemic atherosclerosis could be due by its effects to lower plasma TC, LDL-c, increase plasma HDL-c and enhances antioxidative defenses against the oxidative stress imposed by hypercholesterolemia.